2018
DOI: 10.1002/mbo3.704
|View full text |Cite
|
Sign up to set email alerts
|

Relative catalytic efficiencies and transcript levels of three d‐ and two l‐lactate dehydrogenases for optically pure d‐lactate production in Sporolactobacillus inulinus

Abstract: As the optical purity of the lactate monomer is pivotal for polymerization, the production of optically pure d-lactate is of significant importance. Sporolactobacillus inulinus YBS1-5 is a superior optically pure d-lactate-producing bacterium. However, little is known about the relationship between lactate dehydrogenases in S. inulinus YBS1-5 and the optical purity of d-lactate. Three potential d-lactate dehydrogenase (D-LDH1-3)- and two putative l-lactate dehydrogenase (L-LDH1-2)-encoding genes were cloned fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…These results were similar to those reported in previous studies on the transcriptional analysis of genes encoding LDHs in S. inulinus . They confirmed that the optical purity of d -lactic acid was regulated by the catalytic efficiency of D-LDH and transcriptional levels of ldh D-encoding genes, which correlated with different neutralizing agents 35 . Although the relative catalytic efficiency of the enzymes responsible for the optical purity of lactic acid produced by Sporolactobacillus strains is poorly understood, the regulation of lactate racemization activity at the transcription level has been reported in four Lactobacillus strains 11 .…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…These results were similar to those reported in previous studies on the transcriptional analysis of genes encoding LDHs in S. inulinus . They confirmed that the optical purity of d -lactic acid was regulated by the catalytic efficiency of D-LDH and transcriptional levels of ldh D-encoding genes, which correlated with different neutralizing agents 35 . Although the relative catalytic efficiency of the enzymes responsible for the optical purity of lactic acid produced by Sporolactobacillus strains is poorly understood, the regulation of lactate racemization activity at the transcription level has been reported in four Lactobacillus strains 11 .…”
Section: Resultsmentioning
confidence: 70%
“…In previous reports on S. inulinus YBS1-5, D-LDH activity was induced by Ca 2+ but slightly inhibited by Mg 2+ , whereas L-LDH activity was inhibited by Ca 2+ but induced by Mg 2+ . Additionally, LDH activity was not affected by Na + or K + 35 . Jia et al reported that D-LDH activity of Leuconostoc mesenteroides was slightly enhanced by K + but not by Mg 2+ , and fructose 1,6-biophosphate did not influence the enzymatic activity, indicating that D-LDH does not contain an allosteric site, similar to the structure of D-LDH from Fusobacterium nucleatum and Pseudomonas aeruginosa 29 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, S. inulinus has attracted the attention of researchers due to its superior productivity of D‐lactate (>180 g L −1 ) with high optical purity (Reddy Tadi et al, 2017 ; Zhao et al, 2014 ). Wu et al ( 2019 ) reported that three D‐LDHs and two L‐LDHs exist in the chromosome of S. inulinus CASD and that these enzymes have different activities for pyruvate reduction. Meanwhile, a D‐lactate dehydrogenase named DLDH744 from S. inulinus CASD was found to have sufficient enzymatic activity to produce PLA with low efficiency ( k cat /Km as 1.49 ± 0.076 mM −1 s −1 ; Wang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%